Melanoma-associated leukoderma and vitiligo cannot be differentiated based on blinded assessment by experts in the field - Lommerts, Janny E.; Teulings, Hansje-Eva; Ezzedine, Khaled; Van Geel, Nanja; Hartmann, Arndt; Speeckaert, Reinhart; Spuls, Phyllis I.; Wolkerstorfer, Albert; Luiten, Rosalie M.; Bekkenk, Marcel W. (Journal of the American Academy of Dermatology, 2016)
Melanoma-associated leukoderma (MAL) is a depigmenting disorder that can occur spontaneously in patients with melanoma. The differences in clinical presentation between MAL and vitiligo are not well defined. This may lead to misdiagnosing MAL as vitiligo, resulting in delayed detection of melanoma.The objective of this study was to assess whether experts in the field can distinguish between MAL and vitiligo, and to assess if discriminative features can be identified.We designed an image comparison study in which 4 experts in the field blindly assessed photographs followed by medical history of 11 patients with MAL and 33 with vitiligo.The assessors misdiagnosed 72.7% of MAL cases and marked 80.0% of them as typical vitiligo. The median age at onset of the leukoderma was higher (55 years, P = .001) in MAL. No discriminative features were found.Sampling bias because of inclusion in tertiary referral center is a limitation.The clinical presentation of leukoderma in patients with melanoma resembles that of vitiligo. We propose "melanoma-associated vitiligo" as the more appropriate term for leukoderma in patients with melanoma. Clinicians should be aware that depigmentation in vitiligo can also be caused by melanoma-associated vitiligo and a total body inspection should be performed.
EVALuna2:19617